2023
DOI: 10.1186/s12929-023-00939-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing hydrogel as an injectable implant: translation in brain diseases

Abstract: Tissue engineering biomaterials are aimed to mimic natural tissue and promote new tissue formation for the treatment of impaired or diseased tissues. Highly porous biomaterial scaffolds are often used to carry cells or drugs to regenerate tissue-like structures. Meanwhile, self-healing hydrogel as a category of smart soft hydrogel with the ability to automatically repair its own structure after damage has been developed for various applications through designs of dynamic crosslinking networks. Due to flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 162 publications
0
11
0
Order By: Relevance
“…The self-healing ability of the hydrogels is a critical factor in the repair of TBI for the prolongation of their service life. , Therefore, a direct visual strategy was used to investigate the self-healing performance of the COCS hydrogels. When two COCS hydrogels of different colors were brought together without external intervention, they seamlessly fused into one entity within a span of 4 h (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The self-healing ability of the hydrogels is a critical factor in the repair of TBI for the prolongation of their service life. , Therefore, a direct visual strategy was used to investigate the self-healing performance of the COCS hydrogels. When two COCS hydrogels of different colors were brought together without external intervention, they seamlessly fused into one entity within a span of 4 h (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…These hydrogels can repeat their hydrogel network rupture-crosslinking through dynamic crosslinking strategies such as hydrogen bonding, ion interactions, host–guest interactions, and coordination bonds. 89 In addition, the ability to self-heal allows for the property of shear thinning, enabling the hydrogel to smoothly fill deep or irregularly shaped wounds through injection. 90,91 Recently, Zhang et al reported a self-healing hydrogel composed of oxidized CS and carboxymethyl CS (Fig.…”
Section: Smart Hydrogels For Wound Bandagingmentioning
confidence: 99%
“…Moreover, implanted biomaterials often trigger neuro‐immune reactions, disrupting the BBB and causing inflammation with plasma and peripheral blood cells entering the ventricle. In the context of CNS injury, injectable biomaterials may be used to repair or replace damaged tissue or to deliver drugs or other therapeutic agents to specific locations within the brain 7 . Nanoparticles (NPs) and microparticles are also potent injectable biomaterials used for brain injury repair.…”
Section: Introductionmentioning
confidence: 99%